IMPLEMENTATION OF THE VIKOR METHOD FOR DECISION MAKING ON THE ELIGIBILITY OF SOCIAL ASSISTANCE IN THE TPS3R AREA OF PRINGSEWU DISTRICT - Mardiyanto, Mardiyanto; Anggraeni, Elisabet Yunaiti; Muslihudin, Muhamad (Jurnal TAM (Technology Acceptance Model), 2024)
Poverty is a major social welfare problem in Indonesia. Various efforts have been made by the government to overcome the main problem of social welfare in accordance with the Republic of Indonesia Constitution Number 11 of 2009 concerning social welfare, such as providing social assistance, social rehabilitation, social security, social empowerment, and social protection. Areas that sometimes reflect the large number of poor and underprivileged people are often located in slum areas on the outskirts of the city which are sometimes free from supervision and control from the local government. The Reduce, Reuse, Recycle Waste Management Site (TPS3R) which is a waste management system and technology that is intended as a solution to overcome the problem of waste and its impacts. Through this TPS3R, not only the problem of environmental pollution caused by waste can be reduced, but also products with economic value are produced from waste that is processed by involving the surrounding community so that it obtains benefits. In addition to involving the community to obtain benefits from the existence of TPS3R, this study will examine the variables that determine the eligibility of social assistance recipients using the Bivariate Person and Alpha-Cronbach methods, the aim is to provide social security to the community in the TPS3R area in maintaining the sustainability of the area to remain clean and healthy. To optimize the determination of the eligibility of assistance recipients in the TPS3R area of Pringsewu Regency, the determining criteria will be applied to a system using the Decision Support System model with the implementation of website-based tool tests. By using a website-based system, poverty alleviation programs in the TPS3R area of Pringsewu Regency can be carried out quickly, effectively and efficiently and on target.